2018
DOI: 10.1002/1878-0261.12390
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 as a functional antagonist of PARP1 inhibitors in tumor cells

Abstract: Poly(ADP‐ribose) polymerase 1 inhibitors alone or in combination with DNA damaging agents are promising clinical drugs in the treatment of cancer. However, there is a need to understand the molecular mechanisms of resistance to PARP1 inhibitors. Expression of HMGA2 in cancer is associated with poor prognosis for patients. Here, we investigated the novel relationship between HMGA2 and PARP1 in DNA damage‐induced PARP1 activity. We used human triple‐negative breast cancer and fibrosarcoma cell lines to demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…HMGA2, which encodes a member of the high mobility group family, was previously shown to be amplified and overexpressed in CRC and contributes to CRC progression 17 , 18 . Besides, HMGA2 upregulation is known to attenuate cell death under genotoxic drug treatment 19 . As HMGA2 is the target gene of PiHL in CRC cells, we sought to investigate whether HMGA2 mediates PiHL-induced CRC chemoresistance.…”
Section: Resultsmentioning
confidence: 99%
“…HMGA2, which encodes a member of the high mobility group family, was previously shown to be amplified and overexpressed in CRC and contributes to CRC progression 17 , 18 . Besides, HMGA2 upregulation is known to attenuate cell death under genotoxic drug treatment 19 . As HMGA2 is the target gene of PiHL in CRC cells, we sought to investigate whether HMGA2 mediates PiHL-induced CRC chemoresistance.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(ADP-ribose) polymerase 1 (PARP-1) is a eukaryotic nucleus enzyme that can bind to DNA damage AP sites and DNA strand breaks by zinc-finger of binding of the PARP-1 N-terminal DNA-binding domain, and the C-terminal catalytic domain of PARP-1 is involved in the poly ADP-ribosylation (PARylation) of DNA binding proteins, thus contributing to the DNA damage repair process. HMGA2 has been reported to function as an antagonist of PARP1 inhibitors in human cancer cells (78). Specifically, HMGA2 colocalises and interacts with PARP1 to increase the activity of PARP1.…”
Section: Hmga2 Promotes Base Excision Repairmentioning
confidence: 99%
“…Our current study investigated a role of HMGA2 in the induction of DNA lesions during the course of genotoxic drug treatment. However, HMGA2 has recently also been implicated in DNA damage repair signaling pathways, thus hinting at important functions in genome stability that act downstream of the formation of DNA lesions (Hombach‐Klonisch et al , ; Natarajan et al , ; Palmieri et al , ). In the context of AML, it will be interesting to investigate in the future whether these functions cooperate in leukemic cells to counteract chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…High‐mobility group AT‐hook 2 possesses three independent DNA binding domains, which preferentially recognize AT‐rich nucleotide sequences in double‐stranded DNA (Pfannkuche et al , ; Reeves and Nissen, ). Besides important regulatory roles in gene expression, in particular during embryonic/fetal development and tumorigenesis/metastasis in the adult organism (Droge and Davey, ; Fusco and Fedele, ; Pfannkuche et al , ; Sgarra et al , ), HMGA2 has also been implicated in DNA base excision repair (Summer et al , ) and DNA damage repair signaling pathways (Hombach‐Klonisch et al , ; Natarajan et al , ; Palmieri et al , ), hinting at important functions for HMGA2 in genome stability following genotoxic stress conditions. In this context, fast proliferation rates of cancer cells enhance DNA replication stress (Gaillard et al , ), and we have recently demonstrated that HMGA2 broadly protects hydroxyurea (HU)‐induced stalled replication forks from collapse into genotoxic DSBs in human cancer and stem cells, thus implying that HMGA2 is also involved upstream of DNA repair processes as a first line of defense to prevent genome instability (Ahmed et al , ; Yu et al , ).…”
Section: Introductionmentioning
confidence: 99%